A Rare Case of Melanosis of the Hard Palate Mucosa in a Patient with Chronic Myeloid Leukemia - Umberto Romeo; Gaspare Palaia; Paolo Junior Fantozzi; Gianluca Tenore; Daniela Bosco (Case Reports in Dentistry)
Imatinib Mesylate, also known as Gleevec or ST1-571, is a tyrosine-kinase inhibitor used as the gold standard medication for the chronic myeloid leukemia (CML); Imatinib has indeed deeply revolutionized the CML therapy allowing most patients to have a good quality of life. Despite its beneficial effects, Imatinib has significant side effects such as mucosal pigmentation. A 72-year-old female having an Imatinib induced mucosal pigmentation is presented: she has been treated with Imatinib since 2003 and only in 2014 discovered, during a routine dental visit, having a pigmented lesion on her hard palate mucosa. Histopathologically, the lesion shows the deposition of fine dark brown spherical bodies within the lamina propria and cloaked in between the collagen fibers. There was no sign of inflammation, hyperplasia, or hemorrhage in the tissue.